Perspectives and Approaches for the Out-of-Plane Testing of Masonry Infill Walls - André Furtado (2020)
It is widely accepted that further and more in-depth research is required on the out-of-plane seismic response of masonry infill walls to increase knowledge regarding this particular behaviour and to develop effective strengthening strategies for preventing their collapse. However, such experimental tests are difficult to perform and the scientific community recognizes the complexity inherent to the test apparatus, loading approaches and loading protocols. At the Laboratory for Earthquake and Structural Engineering (LESE), several efforts were carried out over the last years towards characterizing the out-of-plane behaviour of full-scale MIW. Two test setups were developed using two different approaches for applying the out-of-plane loadings. This manuscript provides an overview of the test setups adopted in the literature by other authors and discusses their implication in the MIW response. Therefore, the considerations assumed in the development of the test setups at the LESE laboratory are provided starting by describing the out-of-plane tests with airbags and after that with pneumatic jacks. Further information regarding both tests setups is described and discussed throughout the manuscript. Experimental results of two specimens tested with both approaches are presented, highlighting the main differences and similarities.